Answer:
x = - 2, x = 3
Step-by-step explanation:
Given
x² - x - 6 = 0
Consider the factors of the constant term (- 6) which sum to give the coefficient of the x- term (- 1)
The factors are + 2 and - 3 , since
2 × - 3 = - 6 and 2 - 3 = - 1 , then
(x + 2)(x - 3) = 0 ← in factored form
Equate each factor to zero and solve for x
x + 2 = 0 ⇒ x = - 2
x - 3 = 0 ⇒ x = 3
Answer: r = -244
Step-by-step explanation:
Answer:
17.32
Step-by-step explanation:
since there is a 5 in the thousandths, we round the 1 in the hundredths up and get 17.32
Answer:
That equation is (2.5×2). The mean of the K is ×2
Answer:
Yes, they are congruent!
Step-by-step explanation:
because they are the same shape meaning they will have the same angle/degree.